2019
DOI: 10.1159/000501965
|View full text |Cite
|
Sign up to set email alerts
|

Active Phagocytosis and Diachronic Processing of Calcium Oxalate Monohydrate Crystals in an in vitro Macrophage Model

Abstract: Background: We previously discovered that renal macrophages (Mφs) phagocytose renal calcium oxalate monohydrate (COM) crystals. This study investigated the processing of engulfed crystals using in vitro models. Methods: J774.1 mouse Mφs were exposed to COM crystals and observed for 24 h using polarized light microscopy with/without cytochalasin B (CB), an inhibitor of phagocytosis, to confirm active crystal phagocytosis. LysoTracker and immunohistochemical staining using transmission electron microscopy for ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Williams et al further investigated monocyte mitochondrial function in human serum specimens and reported significantly reduced monocyte mitochondrial maximal respiration, reserve 2). Internalized COM crystals become surrounded by phagosomes that fuse with lysosomes to promote dissolution and spontaneous elimination (29). Mj functions have also been investigated in RTEC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams et al further investigated monocyte mitochondrial function in human serum specimens and reported significantly reduced monocyte mitochondrial maximal respiration, reserve 2). Internalized COM crystals become surrounded by phagosomes that fuse with lysosomes to promote dissolution and spontaneous elimination (29). Mj functions have also been investigated in RTEC.…”
Section: Resultsmentioning
confidence: 99%
“…The authors confirmed the diachronic elimination of engulfed COM crystals in Mφs ( Figure 2 ). Internalized COM crystals become surrounded by phagosomes that fuse with lysosomes to promote dissolution and spontaneous elimination ( 29 ). Mφ functions have also been investigated in RTEC.…”
Section: Resultsmentioning
confidence: 99%
“…Non-polarized macrophages were designated as M0 phenotype. In vitro studies have demonstrated that M0 macrophages were able to internalize and eliminate COM crystals via phagocytosis [ 35 , 36 ]. M0 macrophages could also affect the function of other cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not assess bone resorptive inflammatory cytokines, such as IL-1β, IL-6, and TNF-α. We have reported that these cytokines can trigger inflammatory macrophage activation and induce renal stone formation in mice and humans (24)(25)(26)(27)(28)(29) . In addition, IL-1β and TNF-α are increased during spaceflight, with a trend for increased IL-6 (30).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that these cytokines can trigger inflammatory macrophage activation and induce renal stone formation in mice and humans. ( 24 , 25 , 26 , 27 , 28 , 29 ) In addition, IL‐1β and TNF‐α are increased during spaceflight, with a trend for increased IL‐6. ( 30 ) Further studies are needed to assess changes in these blood and urinary cytokines as risk factors for renal stone formation during spaceflight.…”
Section: Discussionmentioning
confidence: 99%